تأثير العازل الحراري في كمية الحرارة المطلوبة لمخمر دفعي مغلق مزود بالطاقة الشمسية في الشروط المعتدلة الحرارة - صلاح داوود; أحمد فارس زيتون (Tishreen University, 2019)
يهدف هذا البحث إلى دراسة تأثير عامل انتقال الحرارة في كمية الحرارة ودرجتها داخل المخمر، وفي الضياعات الحرارية في المخمر وفق الشروط المعتدلة الحرارة، حيث تمت دراسة مخمر مكشوف، وقياس درجة الحرارة المحيطة به، وحساب كمية الحرارة المقدمة إلى المخمر من اللاقط الشمسي، وتأثير ذلك في تغير درجة حرارة المخمر؛ وذلك عند سماكات مختلفة من العازل الحراري بغية الوصول إلى عامل انتقال الحرارة الأمثل في هذه الشروط. The purpose of this paper is to study  the impact of heat transfer on temperature quantity and inner temperature of digester and the heat losses in the digester in accordance with normal  temperature conditions, where the closed digester are studied and the surrounding  temperature are measured, and the heat quantity given to digester  form solar collector is calculated and so is the impact all these points on digester temperature  variety different in thickness of thermal isolator in order to achieve the optimal heat transfer factor in these conditions.